G450(P) An uncommon cause of deranged thyroid function in a family line. (27th April 2016) - Fordham, J; Lwin, P; Kumar, Y; Moran, C; Chatterjee, K
Abstract : Resistance to Thyroid Hormone (RTH) describes the condition of reduced receptor responsiveness to thyroid hormone in the presence of its sufficient production. Since the term was first used in 1967, over 3000 cases have been discovered, the majority of whom have a mutation in the Thyroid Hormone Receptor β (THRβ) gene. More recently, the term 'Impaired Sensitivity to Thyroid Hormone' has been proposed to encompass the various genetic causes and clinical presentations of this condition. In this report, a case series of a mother and her two children is described, of a familial mutation causing RTH. The condition was first diagnosed in the mother, being then without children, following markedly elevated thyroid hormone levels on a screening test for menstrual irregularity. Genetic sequencing revealed that she was heterozygous for a mutation Cys446Arg in the THRβ gene. Because of this finding, the woman's two children were screened for thyroid dysfunction in early infancy. Both children were born at term, with birth weights around 9 th centile, and were seen post-natally for thyroid function tests. The first child, a boy now aged three years, had on day ten of life a free T4 level of 51.7 pmol/L and Thyroid Stimulating Hormone (TSH) level of 8.4 miu/L. The second child, a girl now aged three months, had on day twelve of life a free T4 level of 71.7 pmol/L and TSH 6.5 miu/L. Both children had normal thyroid peroxidase antibody levels. Neither child has raised concerns regarding growth velocity on regular outpatient review. The first child was referred for Speech and Language Therapy assistance at two years of age for concerns regarding vocabulary and pronounciation. He was discharged after one year. Apart from this input, no further developmental concerns have been raised. This case report emphasises the need for a high degree of suspicion when faced with elevated T4 without suppression of TSH in the context of a family history of thyroid disease.